SPERM MORPHOLOGICAL ASSESSMENTS OF FRIESIAN HOLSTEIN BULL SEMEN COLLECTED FROM THREE ARTIFICIAL INSEMINATION CENTERS IN INDONESIA - Purwantara, B.; Arifiantini, R.I.; Riyadhi, M. (Diponegoro University, 2010)
Morphologically abnormal sperm in semen has been associated with the sub fertility and sterilityfor many years. This study assessed the sperm morphology of Friesian Holstein bull semen which wascollected from three Artificial Insemination centers in Indonesia. Total of 22 bulls were used in thisstudy; an ejaculate from each bull was examined. Three to four glass slides were prepared for each bullsample; a drop of semen was placed on each glass slide, smeared, and air-dried. The smeared sampleswere stained with carbolfuchsin-eosin (Williams stain). Morphological abnormality types were recordedfrom total of 500 spermatozoa. Results demonstrated that all 22 bulls had low sperm abnormality(<10%). Pearshaped was the most frequently type of sperm abnormality found in the samples(0.81±0.93%); while detached head was the lowest (0.01±0.04%).